Vloga medicinske sestre pri preprečevanju bolnišničnih okužb - Črnila, Tamara (Obzornik zdravstvene nege, 2002)
The prevalence of methicillin-resistant Staphylococcus aureus (MRSA) is increasing in most hospitals worldwide and is the consequence of hygienic measures. Role of the nurse in preventing nosocomial infections is enormous, because of the close contact with the patient. With this study we wanted evaluate the knowledge of the nurses about hospital-acquired infections. We included 30 nurses from the surgical ward of the General hospital dr. Jože Potrč in Ptuj. Study results showed good basic knowledge of hygiene, only in hand desinfection most nurses have not confidence. The majority of nurses havealready taken care of patients with MRSA. 77 % of nurses had fears of infection with MRSA. Good informed health care worker is an important factor in preventing nasocomial infections.
Keywords: bolnišnice; Cross infection; Infekcija navzkrižna; infekcije; medicinske sestre; Methicillin resistance; Meticilinska rezistenca; Nursing; Prevention and control; Stafilokokne infekcije; Staphylococcal infections; Staphylococcus aureus; Transmission; zdravstvena nega